The Third Place as an Evolving Concept for Hospitality Researchers and Managers. (September 2019) - Sandiford, Peter John
This article revisits the concept of the third place, critically evaluating its theoretical foundations and continued relevance to social analysis and hospitality, arguing that it can contribute to scholarly understanding of human sociability and community, as well as inspiring service providers. The article explores actual and potential hospitality applications from researcher and practitioner perspectives, also considering a possible hospitable symbiosis from a third place perspective. Its original definition, though providing an important foundation, is driven, in part, by subjective value judgments. The article concludes that the conceptualization of third place requires broadening to include more places where people can socialize, away from first (home) and second (work) places, without delimiting this definition ideologically. This reconceptualization implies, rather than prescribes, informality, neutrality, and inclusiveness within this convivial environment with community maintenance as a primary outcome.